Artificial induction of chlorosis symptom through the silencing of chloroplast genes in transgenic tobacco - and KAPPEI KOBAYASHI, SACHIN ASHOK BHOR, MD. SHAMIM AKHTER (Indian Phytopathology, 2016)
Chlorosis or yellowing is a common feature in plant virus diseases. To study the mechanism underlying virus-induced chlorosis, we previously generated an inducible transgenic tobacco expressing Cauliflower mosaic virus Tav protein and suggested the involvement of host response in chlorosis development. In contrast, studies have shown that the silencing of chloroplast protein genes by antiviral siRNA has a role in chlorosis induction. To comparably analyze these mechanisms of chlorosis, we established Dexamethasone inducible silencing of chloroplast Hsp90 and Magnesium protoporphyrin chelatase subunit I genes by using hairpin RNA and artificial microRNA, respectively. Transgenic tobacco lines showed chlorosis on selection media containing Dexamethasone. RT-PCR analysis confirmed the decreased mRNA levels at 2 days, and visible chlorosis symptoms were observed in 7 days after Dexamethasone treatment in 3-week-old transgenic plants. Comparative analysis of these transgenic plants with iTav-tobacco is expected to promote our understanding on chlorosis symptom development.